Numerical Analysis of Aeration Flow by Using Finite Differences Method on The Substances Heap Model in Storage - Yanto, Asmara (ITP Press - Institut Teknologi Padang, 2017)
The substances heap in storage requires good air flow to keep condition of the substances; particularly they are sensitive substances to specific properties of air that flow around it such as velocity and pressure. Commonly, properties of air in storage flow with low velocity and pressure that called with ?aeration flow?. At this article, an analysis have done to two-dimensions aeration flow of substances heap modelling in storage where position of inlet aeration at middle-top boundary and position of outlet aeration at left-bottom and right-bottom boundaries. Analysis done by focused to distribution of aeration volume flow rate using numerical analysis as potential flow with finite difference method. Distribution of aeration volume flow rate that determined from various of substances height to storage height percentage make different aeration flow contour. A substance height to storage height percentage that makes level of uniformity of colours that almost flattens of aeration flow contour is a compatible variable in placing substances in storage.